2022
DOI: 10.3389/fnut.2022.982032
|View full text |Cite
|
Sign up to set email alerts
|

Circulating trace elements status in COVID-19 disease: A meta-analysis

Abstract: Trace elements are a group of essential metals or metalloids, which are necessary for life, and present in minute amounts. Despite substantial researches highlighting the importance of trace elements in Coronavirus disease 2019 (COVID-19) diseases, a thorough evaluation of the levels of circulating trace elements is lacking. Therefore, we conducted a systematic review and meta-analysis to evaluate the trace element status (Zn, Fe, Cu, Mg, and Se) in COVID-19 disease. We also assessed the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…It is well established that deficiency of both Mg and other trace elements can result in abnormal cellular function or damage by increasing or decreasing susceptibility to infections, and negatively affecting the respiratory system [ 16 ]. Trace elements are a group of essential metals that include Mg, zinc (Zn), iron (Fe), copper (Cu), and selenium (Se) [ 17 ]. Mg is an essential divalent cation required for various metabolic and biochemical functions, with a potential role in the pathogenesis of COVID-19 by contributing to proper immune, vascular, and pulmonary function [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that deficiency of both Mg and other trace elements can result in abnormal cellular function or damage by increasing or decreasing susceptibility to infections, and negatively affecting the respiratory system [ 16 ]. Trace elements are a group of essential metals that include Mg, zinc (Zn), iron (Fe), copper (Cu), and selenium (Se) [ 17 ]. Mg is an essential divalent cation required for various metabolic and biochemical functions, with a potential role in the pathogenesis of COVID-19 by contributing to proper immune, vascular, and pulmonary function [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Zn levels in each of the recovered samples were slightly lower than the control samples, which was a significant difference. Notably, many recent studies had reported that individuals with lower levels of Zn were more likely to get bacterial and viral infections, including COVID-19 [1] , [2] , [3] , [16] . Moreover, COVID patients with a Zn deficiency had a higher rate of complications and needed longer hospital stays [9] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 mediated increases in liver ceruloplasmin synthesis and release, an acute phase protein, cause these alterations in Cu metabolism. Therefore, reporting high level of Cu in infected patients is potentially attributed to the severe inflammatory responses that could lead to an increase in the concentration of toxic free radicals and consequently increase oxidative stress [1] , [24] , [25] , [26] . This potentially occurs due to the roles of Cu as a cofactor in several enzymes, such as superoxide dismutase, and also to the role of Cu in performing several tasks, such as cell defense against ROS- induced harm, anti-oxidative processes, and O 2 and electron transport in the respiratory chain [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency in Se was recorded in several health disorders caused by viruses, including COVID-19 [ 35 , 55 ]. Recent studies revealed that COVID-19 patients have lower circulating levels of iron (Fe), zinc (Zn), and Se [ 58 ]. Se supplementation in COVID-19 patients has been useful in preventing disease progression [ 59 ].…”
Section: The Role Of Se In the Prevention And Treatment Of Health Dis...mentioning
confidence: 99%